2015
DOI: 10.1038/ncomms8502
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide association of polycystic ovary syndrome implicates alterations in gonadotropin secretion in European ancestry populations

Abstract: Polycystic ovary syndrome (PCOS) is a common, highly heritable complex disorder of unknown aetiology characterized by hyperandrogenism, chronic anovulation and defects in glucose homeostasis. Increased luteinizing hormone relative to follicle-stimulating hormone secretion, insulin resistance and developmental exposure to androgens are hypothesized to play a causal role in PCOS. Here we map common genetic susceptibility loci in European ancestry women for the National Institutes of Health PCOS phenotype, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
237
3
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 353 publications
(260 citation statements)
references
References 69 publications
(132 reference statements)
13
237
3
7
Order By: Relevance
“…Our data demonstrate that, in particular, extraovarian neuroendocrine AR sites of androgen action are predominantly involved in the pathogenesis of multiple key PCOS characteristics. This provides strong experimental support for recent GWAS findings that highlight the importance of gonadotropin action in the genetic origins of susceptibility to PCOS (24)(25)(26). In concert, these Serum concentrations of dihydrotestosterone, testosterone, dehydroepiandrosterone, 5α-androstane-3α,17β-diol, 5α-androstane-3β,17β-diol, progesterone, luteinizing hormone, and follicle-stimulating hormone.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our data demonstrate that, in particular, extraovarian neuroendocrine AR sites of androgen action are predominantly involved in the pathogenesis of multiple key PCOS characteristics. This provides strong experimental support for recent GWAS findings that highlight the importance of gonadotropin action in the genetic origins of susceptibility to PCOS (24)(25)(26). In concert, these Serum concentrations of dihydrotestosterone, testosterone, dehydroepiandrosterone, 5α-androstane-3α,17β-diol, 5α-androstane-3β,17β-diol, progesterone, luteinizing hormone, and follicle-stimulating hormone.…”
Section: Discussionsupporting
confidence: 78%
“…1). Our findings highlight the importance of extraovarian AR-mediated androgen actions in the origins of PCOS features, which is strongly supported by findings from recent genome-wide association studies (GWAS) of PCOS highlighting the importance of gonadotropins in PCOS (24)(25)(26).…”
supporting
confidence: 84%
“…The advent of large-scale GWAS with their stringent statistical thresholds has brought robust new insights, although as yet these have been limited to adult PCOS cases and their direct relevance to adolescent PCOS is yet to be established. The first GWAS for PCOS were performed in Han Chinese populations [92, 93]; while the identified genomic loci were replicable in that population, their effects estimates are consistently smaller in Caucasian PCOS cases, possibly due to population differences in genetic architecture or even PCOS sub-phenotypes [94, 95]. …”
Section: A Pathophysiologymentioning
confidence: 99%
“…Interestingly, genetic studies have revealed a significant overlap of findings when different diagnostic criteria of PCOS have been applied, highlighting greater homogeneity than previously appreciated. 16,56,57 Clinical features and co-morbidities…”
Section: Recent Insights From Genetic Studiesmentioning
confidence: 99%